Efektifitas Konseling terhadap Pengetahuan dan Sikap Ibu dalam Pencegahan Stunting di Puskesmas Bawomataluo Nias Selatan - Mutiara Fanny Ginting; Parida Hanum; Maharani Maharani; Onis Pertiwi; Mariani Mariani (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Stunting is the growth and development of a child's height that is not the same as his age caused by malnutrition and lack of parental knowledge. The purpose of the study was to determine the effectiveness of counseling on maternal knowledge and attitudes in preventing stunting at the Bawomataluo Public Health Center in South Nias in 2021. The research method is a quasi-experimental design with one group pretest-posttest and a control group. The number of samples was 30 pregnant women, 15 intervention groups and 15 control groups. Methods of collecting data using a questionnaire with the Wilcoxon test. The results of statistical tests obtained knowledge and attitudes p value 0.001 (p <0.05) which means that there is a significant effectiveness before and after being given counseling on stunting prevention. Analysis of the data found knowledge and attitudes before counseling, namely the majority lack of knowledge, namely 9 people (60%) and the minority enough 2 people (40%) and the majority attitude was negative 8 people (53.3%) and the minority positive 7 people (46.6%). After counseling, it was found that the majority had good knowledge, namely 11 people (73.3%) and the minority was sufficient 4 people (26.6%) and the majority attitude was positive 13 people (86.6%) and the minority was negative 2 people (13.3%). From the results above, there is an effectiveness of counseling on knowledge and attitudes of mothers about stunting prevention. Researcher's suggestion through health counseling can increase mother's insight.